A MnIIMnIII‐Peroxide Complex Capable of Aldehyde Deformylation. Issue 17 (27th March 2019) - Magherusan, Adriana M.; Kal, Subhasree; Nelis, Daniel N.; Doyle, Lorna M.; Farquhar, Erik R.; Que, Lawrence; McDonald, Aidan R.
Abstract: Ribonucleotide reductases (RNRs) are essential enzymes required for DNA synthesis. In class Ib Mn2 RNRs superoxide (O2 .− ) was postulated to react with the Mn II 2 core to yield a Mn II Mn III ‐peroxide moiety. The reactivity of complex 1 ([Mn II 2 (O2 CCH3 )2 (BPMP)](ClO4 ), where HBPMP=2, 6‐bis[(bis(2‐pyridylmethyl)amino]methyl‐4‐methylphenol) towards O2 .− was investigated at −90 °C, generating a metastable species, 2 . The electronic absorption spectrum of 2 displayed features ( λ max =440, 590 nm) characteristic of a Mn II Mn III ‐peroxide species, representing just the second example of such. Electron paramagnetic resonance and X‐ray absorption spectroscopies, and mass spectrometry supported the formulation of 2 as a Mn II Mn III ‐peroxide complex. Unlike all other previously reported Mn2 ‐peroxides, which were unreactive, 2 proved to be a capable oxidant in aldehyde deformylation. Our studies provide insight into the mechanism of O2 ‐activation in Class Ib Mn2 RNRs, and the highly reactive intermediates in their catalytic cycle. Abstract : Nucleophilic reactivity : The reaction of a Mn II 2 complex with superoxide yielded a Mn II Mn III ‐peroxide complex which mimics intermediates in class Ib Mn2 ribonucleotide reductases. The Mn II Mn III ‐peroxide species displayed an unexpected nucleophilic character in aldehyde deformylation.